Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jcb.26605
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Analgesic effects of microRNA‐129‐5p against bone cancer pain through the EphB1/EphrinB2 signaling pathway in mice

Abstract: The study aims to investigate the analgesic effects of microRNA-129-5p (miR-129-5p) on bone cancer pain (BCP) by targeting Eph receptor B1 (EphB1) through the EphB1/EphrinB2 signaling pathway. BCP mice models were established, and C3H/HeJ female mice were classified into the normal, blank, negative control (NC), miR-129-5p mimics, miR-129-5p inhibitors, EphB1 knockout (KO), and miR-129-5p inhibitors + EphB1 KO groups. Quantitative reverse transcription polymerase chain reaction and Western blot analysis were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…MiR-129 has long been studied as a biomarker for cancers such as gastric, rectal, and bladder cancer. In this signaling pathway in mice (33). Our results confirmed that miR-129 may be closely related to the analgesic effect of morphine.…”
Section: Discussionsupporting
confidence: 77%
“…MiR-129 has long been studied as a biomarker for cancers such as gastric, rectal, and bladder cancer. In this signaling pathway in mice (33). Our results confirmed that miR-129 may be closely related to the analgesic effect of morphine.…”
Section: Discussionsupporting
confidence: 77%
“…The pathogenesis of BCP is related to a multitude of genetical and biological regulators [3,4], however, recently an increasing amount of evidence support that microRNAs (miRNAs) play an essential role as regulators in BCP development [5][6][7][8]. MiRNAs can regulate multiple pathological and physiological processes, including differentiation, morphogenesis, apoptosis, proliferation, and survival on the protein level, through binding to the 3' untranslated region of their target mRNAs [9].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-125b was chosen for further study, and the authors found that miR-125b was essential for functional recovery, and it guides correct regeneration of axons through the lesion site via direct downstream target Sema4D in axolotls [14]. MiR-129-5p acts as a tumor suppressor and has been widely studied in different cancer including colon cancer [15], non-small cell lung cancer [16], bone cancer [17], and breast cancer [18]. However, the role of miR-129-5p in the acute SCI still remains unclear.…”
Section: Discussionmentioning
confidence: 99%